Making Sami Seascapes Matter : ethno-ecological governance in coastal Norway - Brattland, Camilla (University of Tromsø, 2012)
The papers and the film of this thesis are not available in Munin: 1. Brattland, Camilla and Nilsen, Steinar: 'Reclaiming indigenous seascapes. Sami place names in Norwegian sea charts', Polar Geography (2011), vol. 34, no. 4:275-297. Available at http://dx.doi.org/10.1080/1088937X.2011.644871 2. Brattland, Camilla: 'Overfishing and cyborgization in Sami fisheries. A case study of the use of traditional knowledge in small-scale fisheries in Porsanger, Norway', (submitted manuscript to Maritime Studies (MAST)). 3. Brattland, Camilla: 'Mapping rights in coastal Sami seascapes', in Arctic Review of Law and Politics (2010) vol. 1 no. 1:28-53. Available at http://lawlib.wlu.edu/CLJC/index.aspx?mainid=1724&issuedate=2011-05-09 4. Brattland, Camilla: 'Fish farming, politics and monster cod. The production of fishers‘ knowledge in the coastal zone', (forthcomming manuscript in Acta Borealia). 5. Brattland, Camilla: 'Sami fishing grounds and the missing layers of the marine environment', (manuscript submitted to Norsk Geografisk Tidsskrift – Norwegian Journal of Geography). Ethnographic film: Wright, Reni and Brattland, Camilla: 'Learning hoavda‘s seascape' (2012), (10:36 min). Norwegian title: 'Hoavda og skårungene'. Wright kunnskapsformidling and Visual Cultural Studies, Department of Archaeology and Social Anthropology, University of Tromsø. Available at the University Library of Tromsø and Center for Sami Studies, University of Tromsø. This thesis addresses the lack of knowledge production on impacts of new marine industries on coastal Sami culture in the Norwegian coastal zone. It asks how Sami culture matters in contemporary Norwegian marine governance, and discusses how ecosystem mapping practices facilitate knowledge production on Sami relations and use of the marine environment. This is done through five papers and a film, focusing on the Porsanger and Lyngen fjords in northern Norway, analyzing 1) the characteristics of Sami fisheries and seascapes, 2) how Sami fisheries are enacted through fisheries ...